Pengembangan Pusat Unggulan Teknologi, Center Of Heavy Equipment Untuk Mempersiapkan Sdm Bidang Mekanik Dan Operator Alat Berat Yang Kompeten - Abdul Hamid; Mohammad Anas Fikri; Ike Dayi Febriana; Laily Ulfiyah; Misbakhul Fatah; Lukman Hadiwijaya; Amin Jakfar; Auliana Diah Wilujeng; Annafiyah Annafiyah; Faizatur Rohmah; Ratna Ayu Pawestri K. D; Septian Dwi Wijaya; Nadiyah Ulfah; Dimas Aryo Wicaksono; Ghopal Ahmad Fachrudin; Eddy Harsono (Journal of Applied Mechanical Engineering and Renewable Energy, 2023)
The low demand for vocational education graduates has led to high unemployment. The low demand for vocational education graduates has led to high unemployment. Vocational college graduates still need to be commensurate with industrial needs. Many Senior High School, Vocational High School, and Vocational College graduates have not been able to find a job for more than six months. Conditions on Madura island worsened this, and the lack of accelerated industrialization even after the Suramadu Bridge was built. Madura has the lowest Human Development Index (HDI) score in East Java. Data from the Central Bureau of Statistics (BPS) Sampang in Figures 2021) shows that the HDI value in 2020 only increased by 0.76 from 2019 of 62.70. Politeknik Negeri Madura (Poltera) together with PT. United Tractors and LSP ABI want to take an active role in improving Madura's HDI by preparing human resources on heavy equipment mechanics through the development of a centre of excellence for technology (PUT) of Heavy Equipment (CHE). Using the causal-comparative method, the researcher observed the impact of each stage on PUT-CHE development activities and reviewed the data to find causal factors and correlations. Poltera took a strategic step by equipping lecturers with virtual training on heavy equipment mechanics (SOBAT Program), organized by PT United Tractors. The SOBAT program has positively impacted heavy equipment engineering graduates in 2022, which has increased significantly. Academic data showed that 13 out of 34 heavy equipment mechanical engineering graduates were employed in leading heavy equipment industries before three months. Other data stated that three lecturers participating in Virtual Training on heavy equipment mechanics were selected as 50 interns at PT United Tractors.